Improving the Machining Process of the Metalwork Industry by Upgrading Operative Sequences, Standard Manufacturing Times and Production Procedure Changes - Monteiro, Carlos (2020)
Manufacturing industries are currently experiencing important changes towards digitization and autonomous production control, which is known as Industry 4.0. However, the profitability of some companies, namely Small and Medium Enterprises (SMEs), and of some industrial sectors does not allow for great investments, meaning that is necessary to undertake simple changes that potentially can lead to significant gains. This is the case for the metalwork company under study, where wastes related to the large parts movement and non-conformities detected before and after the parts delivered to the customers have been identified. The elimination of these wastes can contribute to a significant increase in the profitability of the company. The use and integration of several Lean tools made it possible to achieve this goal for this company. Amongst other improvements on productivity and waste reducing, a 59% reduction in the time required to move parts of up to 1000 kg, a reduction of 2.04% on the external non-conformities (i.e. on non-conformities detected outside the company) and 3.99% on the internal non-conformities, was achieved.